2014
DOI: 10.1089/dia.2013.0208
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 12 Blood Glucose Monitoring Systems for Self-Testing: System Accuracy and Measurement Reproducibility

Abstract: In summary, 83% of the systems fulfilled with the evaluated test strip lot minimum system accuracy requirements of DIN EN ISO 15197:2003. Each of the tested systems showed acceptable measurement reproducibility. In order to ensure sufficient measurement quality of each distributed test strip lot, regular evaluations are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 15 publications
4
63
0
3
Order By: Relevance
“…6,7,18 Noteworthy comparative studies reported good performance of CXT-BGMS when ISO 15197:2013 accuracy limits were applied. 16,17,19 In a recent multicenter study conducted in 21 hospitals under routine conditions using 2100 leftover blood samples, 20 CXT-BGMS results were remarkably congruent with the present data. The ISO accuracy limits and CEG results similarities corroborate the generalizability of the performance data of the CXT-BGMS in different hospital environments.…”
Section: Discussionsupporting
confidence: 88%
“…6,7,18 Noteworthy comparative studies reported good performance of CXT-BGMS when ISO 15197:2013 accuracy limits were applied. 16,17,19 In a recent multicenter study conducted in 21 hospitals under routine conditions using 2100 leftover blood samples, 20 CXT-BGMS results were remarkably congruent with the present data. The ISO accuracy limits and CEG results similarities corroborate the generalizability of the performance data of the CXT-BGMS in different hospital environments.…”
Section: Discussionsupporting
confidence: 88%
“…This was one factor that led to a surge in the number and types of "generic" BGM meters. In some cases, when meters sourced from retail distribution channels were tested, the generic testing systems meters demonstrated dramatically inferior accuracy and precision compared to systems from major branded manufacturers (56)(57)(58)(59). These generic meters showed sufficient performance data to obtain initial FDA clearance; however, they may not have maintained adequate performance over time, in part due to poor quality control leading to large between-lot variability in test strips.…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
“…Several published studies have compared BGM brands and models by name during headto-head testing (56,57,136,(145)(146)(147)(148). For clinicians and consumers, MARD provides an excellent measure of accuracy and precision when evaluating a BGM (134).…”
Section: Iso Standardsmentioning
confidence: 99%
See 2 more Smart Citations